Report from the European Veterinary Libraries Group’s meeting 14th EAHIL Conference. 11-13 June 2014, Rome (Journal of EAHIL, 2017)
The EVLG (European Veterinary Libraries Group) had a very nice meeting outside the conference centre on the grass(and in the shade!).We elected some new board members and the board is now:Chair: Michael Eklund, SwedenVicechair: Raisa Iivonen, FinlandSecretary: Fiona Brown, Great BritainWebmanager: Eva Orban, HungaryTreasurer: Derek Halling, USA.